Rapid Information from Household High-Frequency Monitoring : Summary of Results from Round 1 - World Bank (Washington, DC: World Bank, 2020)
This brief presents the main findings from the first of eight rounds of a nationally representative survey of 1,500 randomly selected households in all states and regions of Myanmar. The surveys were undertaken by conducting a 20-minute phone call between 18 May 2020 and 3 June 2020.